Preparation of a Silicon/MXene Composite Electrode by a High-Pressure Forming Method and Its Application in Li+-Ion Storage - Yonghao Liu; Dawei Zhao; Lujia Cong; Yanfeng Han; Mingdi Fu; Xiaoxin Wu; Junkai Zhang (Molecules, 2025)
The main component of high-capacity silicon-based electrodes is silicon powder, which necessitates intricate processing to minimize volume growth and powder separation while guaranteeing the ideal Si content. This work uses the an situ high-pressure forming approach to create an MXene/m-Si/MXene composite electrode, where MXene refers to Ti3C2TX, and m-Si denotes two-phase mixed nano-Si particles. The sandwich shape promotes silicon’s volume growth and stops active particles from spreading. The conductive structure of Ti3C2TX MXene increases the efficiency of charge transfer while reducing internal resistance. After 100 cycles, the composite electrode’s original capacity of 1310.9 mAh g−1 at a current density of 0.5 A g−1 is maintained at 781.0 mAh g−1. These findings lay the foundation for further investigations into Si matrix composite electrodes.